2022
DOI: 10.1155/2022/7396310
|View full text |Cite|
|
Sign up to set email alerts
|

The Efficacy of Mannitol Combined with 6-Aminocaproic Acid in the Treatment of Patients with Cerebral Hemorrhage and Its Impact on Immune Function

Abstract: Objective. To determine the efficacy of Mannitol combined with 6-aminocaproic acid in the treatment of patients with cerebral hemorrhage, as well as its impact on the immune system. Methods. The study subjects consisted of 122 patients with early intracerebral hemorrhage treated in our hospital from April 2019 to April 2022. Based on the different admission times, the participants were randomly divided into the control group and the study group in a ratio of 1:1. 6-Aminocaproic acid was used to treat patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…With its high mortality rate and rapid progression, HICH presents considerable challenges in treatment [4]. Pharmacotherapy in clinical practice aims to reduce intracranial pressure and alleviate edema [5]. However, the efficacy of drugs varies significantly among different agents.…”
Section: Introductionmentioning
confidence: 99%
“…With its high mortality rate and rapid progression, HICH presents considerable challenges in treatment [4]. Pharmacotherapy in clinical practice aims to reduce intracranial pressure and alleviate edema [5]. However, the efficacy of drugs varies significantly among different agents.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%